2008
DOI: 10.1002/gps.2092
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of help‐seeking behaviour in subjects with subjective memory complaints at a memory clinic: a case‐control study

Abstract: Lower memory self-efficacy and quality of life, deterioration in daily functioning, and worries due to a positive family history for dementia are factors that determine why subjects with SMC seek medical attention. This information may be useful for the development of interventions for these subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 25 publications
1
52
0
Order By: Relevance
“…their memory that may represent the type of patient most likely to present to clinicians. A recent study comparing older adults with subjective memory complaints who sought medical attention with those who did not found no differences in terms of depressive and anxiety symptoms or personality factors, although memory self-efficacy and quality of life scores were lower in the group that sought help (Ramakers et al, 2009). Whilst every effort was made to exclude psychiatric and personality disorder, it is possible that SCI participants had mild symptomatology which was undetected by a psychiatric interview but could have influenced brain activation.…”
Section: Limitationsmentioning
confidence: 99%
“…their memory that may represent the type of patient most likely to present to clinicians. A recent study comparing older adults with subjective memory complaints who sought medical attention with those who did not found no differences in terms of depressive and anxiety symptoms or personality factors, although memory self-efficacy and quality of life scores were lower in the group that sought help (Ramakers et al, 2009). Whilst every effort was made to exclude psychiatric and personality disorder, it is possible that SCI participants had mild symptomatology which was undetected by a psychiatric interview but could have influenced brain activation.…”
Section: Limitationsmentioning
confidence: 99%
“…26,[35][36][37][38] (2) Severity of the disease: Studies examining family caregivers' reasons for HS as well as those examining lay persons, found that increased severity of the disease, as reflected mainly in increased behavioral problems, was one of the main facilitators to HS. 19,25,35,41 (3) Beliefs: Several studies mentioned fatalistic and cultural beliefs as barriers to HS. 19,25,35,41 (3) Beliefs: Several studies mentioned fatalistic and cultural beliefs as barriers to HS.…”
Section: Factors Affecting Hsmentioning
confidence: 99%
“…They also lack knowledge of the early signs and of available support resources. Finally, sociodemographic determinants, such as gender and educational level, family history, and the living situation are related to delayed diagnosis (Tijhuis et al, 1990;Mackenzie et al, 2006;Pentzek et al, 2009;Ramakers et al, 2009;Tedstone Doherty and Kartalova-O'Doherty, 2010). In practice, it usually takes a long time or several appointments for a thorough assessment and examination before a diagnosis is made (Iliffe et al, 2003;Downs and Bowers, 2008;Iliffe et al, 2009).…”
Section: Introductionmentioning
confidence: 99%